IN VIVO BIODISTRIBUTION OF 99mTc-MDP FOR EARLY OSTEOPOROSIS MONITORING IN OVARIECTOMIZED BALB/C MICE - Ahmad Kurniawan; Yulianne Mahesa; Teguh Hafidz Ambar Wibawa; Iswahyudi Iswahyudi; Isti Daruwati; Aang Hanafiah Wangsaatmadja (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2020)
Technetium-99m Methylene Diphosphonate (99mTc-MDP) has been utilized in a variety of clinical situations to identify bone areas due to the strong affinity of hydroxyapatite crystals in the mineral phase of the bone with the diphosphonate compounds. Osteoporosis is a disease characterized by decreased bone mass and increased fracture risk and represents a significant population health issue. It has been observed that 99mTc-MDP can be used for bone scintigraphy especially in case of bone cancer, but biodistribution study of 99mTc-MDP on ovariectomized mice for early monitoring of osteoporosis model remains unclear. Therefore, we aimed to investigate the biodistribution of 99mTc-MDP both in normal and ovariectomized mice. The experiment was performed on BALB/c mice weighing approximately 30 g. Mice were divided into a normal and ovariectomized group. After the first, second and third hours, mice were euthanized using the accepted protocol and the tissue of interest was collected. All tissue and blood were weighed using an analytical scale and counted for radioactivity using Automatic Gamma Counter with NaI(Tl) detector. Administration of 99mTc-MDP showed in normal mice compared with an animal model of osteoporosis, there are significant differences at 1 hour post-injection from (20.32±1.38) %ID/g decreased to (7.42±2.61) %ID/g, 2 hours from (13.75±0.01) %ID/g to (5.25±0.25) %ID/g and 3 hours from (12.18±1.44)%ID/g to (4.86±1.34) %ID/g uptake in the bones with (p<0.05). This study can be a consideration for the clinical application of 99mTc-MDP for early detection of osteoporosis conditions by looking at bone uptake and become a concern in the application for bone scintigraphy if the patient is indicated osteoporosis because it will affect visualization of the organ.